Penggunaan Metode Karyawisata untuk Meningkatkan Pemahaman Konsep pada Materi Keanekaragaman Hayati dan Upaya Pelestariannya - Nurmaliah Nurmaliah (Biotik, 2019)
The purpose of this study was to determine the increase in students' understanding of biodiversity material and its preservation efforts through the field trip method. This research was carried out in the MTsN Model Banda Aceh, while the field trip location is the Mata Ie Forest in Darul Imarah sub-district and the Taman Rusa in Suka Makmur sub district, Aceh Besar. The research method is experimental method. The samples in this study were 2 randomly determined classes consisting of one experimental class of 36 students using the field trip method and one control class of 36 students with the expository method. The data analysis technique was carried out with the z-test with SPSS 16.0. The results showed that the concept understanding for the control class was 70 and the experimental class was 76. There was a significant difference between the application of the field trip method and the expository method to students' understanding of the biodiversity concept. It can be concluded that the application of the field trip method can increase student interest in learning, specifically for biodiversity material and its preservation efforts.